Simulated real-ear measurements of benefit from digital feedback suppression. - Olsen Sø (International Journal of Audiology, 2008)
Digital feedback suppression (DFS) enables users of hearing instruments (HI) to benefit from amplification levels that normally would provoke whistling or poor sound quality. A standardized test for the measurement of DFS benefit is not available. This paper proposes and evaluates an objective method for assessment of extra feedback-free amplification (headroom) provided by a given DFS. It is shown that the whistle-free loop gain can be calculated from data obtained with simulated real-ear measurements with the modified pressure method. Test-retest trials were carried out to assess the reliability of the proposed method. Also, a method was developed for defining an appropriate gain level at which the proposed measurement should be carried out. It is concluded that the proposed method needs to be modified to provide useful information.